PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF BERBANTUAN CANVA MENGGUNAKAN MODEL ADDIE PADA MATERI PERKEMBANGBIAKAN MAKHLUK HIDUP KELAS VI SDN 069 SIHARJULU - Yosep Epron Valentino Sinaga; Lidia Simanihuruk; Elvi Mailani; Nurhairani; Lala Jelita Ananda (STKIP Subang, 2026)
This study aims to develop an interactive video learning media assisted by Canva using the ADDIE model on the topic of Living Things Reproduction for sixth-grade students at SDN 069 Siharjulu. The research employed a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved 25 sixth-grade students as the research subjects. Data were collected through expert validation questionnaires, student response questionnaires, and learning outcome tests (pre-test and post-test). The results showed that: (1) the validity of the media reached 93% (Very Feasible) from the media expert and 90% (Very Feasible) from the content expert; (2) the practicality was rated 95% (Very Practical) by the teacher and 94% (Very Practical) by students; and (3) the effectiveness was demonstrated by an increase in the average learning outcome from 55.7 (pre-test) to 69.4 (post-test), with N-Gain score in the Very Effective category. These findings conclude that interactive video learning media assisted by Canva is valid, practical, and effective for use in science learning on the topic of Living Things Reproduction in sixth grade.